Catheter Ablation of Atrial Fibrillation - Chi Keong Ching, MD (Journal of Arrhythmia, 2007)
Atrial fibrillation is the most common arrhythmia encountered in clinical practice and can result in significant morbidity and mortality. Catheter ablation has become a feasible therapeutic option for the management of this complex and challenging arrhythmia. In this article, we have discussed the mechanism of atrial fibrillation, different imaging modalities used for atrial fibrillation ablation, different ablation strategies targeting non-pulmonary veins, complications associated with atrial fibrillation ablation and its management, alternative energy sources for ablation and new antiarrhythmic drugs.